China in a secular age coping with the legacy of a religious state - Laliberté, André 1959- (Brill, 2021)
Is China truly a secular state? André Laliberté puts this widely held perception to the test, arguing that we must first broaden our definitions if we are to comprehend fully the religious nature of the Chinese state. From there, Laliberté presents the long tradition of Chinese statecraft, which has involved different forms of intermingling between religion and state, and describes how the Communist Party perpetuates this institutional intertwinement despite its materialist philosophy. He then explores the variety of forms in which societies with a Chinese heritage outside of the People’s Republic of China are moving beyond this mutual entanglement between religion and state.
Literaturverzeichnis: Seite 74-85
Keywords: Zhong guo gong chan dang; Geschichte; Säkularismus; Religion; China; godsdienstvrijheid